1996
DOI: 10.1128/mcb.16.5.2204
|View full text |Cite
|
Sign up to set email alerts
|

Pre-mRNA Topology Is Important for 3′-End Formation in Saccharomyces cerevisiae and Mammals

Abstract: Various signal motifs that are required for efficient pre-mRNA 3'-end formation in the yeast Saccharomyces cerevisiae have been reported. None of these known signal sequences appears to be of the same general importance as is the mammalian AAUAAA motif. To establish the importance of yeast pre-mRNA termini in 3'-end formation, the ends of a pre-mRNA transcript synthesized in vitro were ligated before incubation in a yeast whole-cell extract. Such covalently closed circular RNAs were not cleaved at their poly(A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…4), of a similar structure to that required for polyadenylation in the human U1A pre-mRNA (Gunderson et al 1994). In some instances, RNA topology is known to play an important role in 3¢-end formation, both in yeasts and in mammals (Irniger et al 1991;Stumpf et al 1996). Therefore, we suggest that polyadenylation sites in wos2 transcripts may be determined by RNA topology.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…4), of a similar structure to that required for polyadenylation in the human U1A pre-mRNA (Gunderson et al 1994). In some instances, RNA topology is known to play an important role in 3¢-end formation, both in yeasts and in mammals (Irniger et al 1991;Stumpf et al 1996). Therefore, we suggest that polyadenylation sites in wos2 transcripts may be determined by RNA topology.…”
Section: Resultsmentioning
confidence: 82%
“…Some sequence motifs have been proposed to play an important role in cleavage and poly(A) site recognition (Stumpf et al 1996), but none of them seems to be of general significance for 3¢-end formation in yeast transcripts (Dichtl and Keller 2001) -perhaps because RNA signals are frequently composed of a combination of sequence and structural motifs. This seems to be the case in wos2.…”
Section: Resultsmentioning
confidence: 99%
“…3). It has already been reported that pre-mRNA topology is important for 3¢ end formation and poly(A) site recognition (van Gelder et al 1993;Graveley et al 1996;Stumpf et al 1996). With this in mind, it is striking that the only two long, hypothetical, stem-loop structures (with a stem of 15 nucleotides) found in the RNA14 sequence (including the 5¢ and 3¢ untranslated sequences) are located at or near the cleavage sites of the short and middle transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…Pol II does not appear to be involved in the poly(A) addition step. The interaction of the CTD with CPSF and CstF (299) may stabilize the cleavage complex or, as proposed by Hirose and Manley (205), have allosteric effects, such as those found for CTD and the capping enzyme (443). This involvement of Pol II in cleavage is consistent with earlier studies showing that protein-encoding mRNAs transcribed by Pol I and Pol III were for the most part not polyadenylated (257,429,432) and with the recent demonstration of the colocalization of CstF and phosphorylated pol II in vivo (439).…”
Section: Cleavage/polyadenylation Machinerymentioning
confidence: 92%
“…The presence of mRNA secondary structure around signal sequences may be important in some yeast genes (222,401), and a long-range interaction of 5Ј and 3Ј untranslated regions has been demonstrated for MFA2 mRNA (130). While the contribution of RNA conformation has not been rigorously investigated for any site, circular RNA substrates are not cleaved in vitro (443).…”
Section: Rna Sequences Which Specify Cleavage Andmentioning
confidence: 99%